The dental workforce in Malaysia: career motivation and expectations amongst senior dental students - Che Musa, Muhd Firdaus (IIUM Press, International Islamic University Malaysia, 2020)
The dental workforce globally is facing unprecedented change as a result of multiple influences. Malaysia, a high-middle-income country, has expanded the number of dental schools in the last decade to ensure that there are a sufficient number of health workers to meet the needs and demands of the population. As the volume of dentists entering the workforce has increased, concerns about the long-term implications of these policies and how this expensively trained dental workforce will be utilised in the future are emerging. There is a need for research informed action in relation to understanding workforce influences, and examining their potential implications and the shape of the future workforce in relation to population need. An understanding of the motivation of current dental students for choosing to study dentistry and their subsequent career expectations may assist with harnessing and retaining their skills. This is the first book in a series of three planned to be published concerning the dental workforce in Malaysia. The aim of this series is to present findings on motivation and short- and long-term career expectations of dental students in the selection of dentistry as a professional career in relation to individual (demographic and socio-economic factors) and school characteristics and make recommendations for the future in relation to serving the population. Senior dental students from 11 schools were invited in early 2013 to complete a questionnaire survey of the Gallagher Motivation Instrument (GMI) to examine career motivation and expectations. Univariate and multivariate analyses of the responses, including confirmatory factor analysis of career motivation, were undertaken followed by descriptive analysis of their career expectations. Three hundred and fifty six final year dental students (83%) across eight schools (73%) responded, comprising 66% of final years in Malaysia in 2013. Five motivational factors were reported with ‘academic’ factors emerging as students’ main motivation to study dentistry. There were some differences in motivation by school sector; either public or private and ethnicity. There was however no variation by sex, family income, age or the school type (established or new). Career expectations focused on specialisation in the short-term (46%) and long-term (59%) for students, with a desire to achieve financial stability and work/life balance. The majority of all respondents (64%) reported a desire to work in the private sector. Only 66.9% of respondents considered working full-time in the long-term with significant difference by sex [male (77.7%) and female (62.5%); (p=0.036)].